The effect of T6 heat treatment on the tensile, impact, and fatigue properties of Al6061-fly ash composites - Zainun Achmad; Al Emran bin Ismail; Harjo Seputro; Eka Marliana (Universitas Negeri Padang, 2026)
This study investigates the effect of controlled precipitation hardening on the mechanical behavior of Al6061–fly ash metal matrix composites fabricated using stir casting and subjected to T6 heat treatment. The specimens underwent solution treatment at 510°C for 1 and 2 hours, followed by oil quenching and artificial aging at 120°C, 140°C, and 160°C for 2 hours. Tensile, Rockwell hardness, impact, and fatigue tests were used to assess the mechanical characteristics, in accordance with ASTM standards, and were supported by microstructural and SEM studies. The findings indicate that T6 treatment greatly improves strength and fatigue tolerance compared with the untreated state. The highest tensile strength and impact energy were achieved under the T6-A2 condition (510 °C for 2 h + aging at 120 °C for 2 h), whereas the longest fatigue life was obtained under the T6-B1 condition (510 °C for 1 h + aging at 140 °C for 2 h). This shows a good balance between strength and toughness, which is related to the formation of fine Mg2Si precipitates and enhanced interfacial bonding. Aging at 120°C resulted in the highest hardness at 510°C (2 hours). Over-aging reduced ductility and impact resistance because of precipitate coarsening. For durable aluminum–fly ash composites, these results show a distinct link between processing, microstructure, and material characteristics.